Caught - Haddix, Margaret Peterson (New York : Simon & Schuster Books for Young Readers, 2012)
When Jonah and Katherine travel to early 1900s Switzerland and Serbia to return Albert Einstein's daughter, Lieserl, to history, her mother Mileva grasps entirely too much about time travel and has no intention of letting her daughter go.
730
Keywords: Einstein-Maric, Mileva, -- 1875-1948 -- Juvenile fiction; Einstein, Albert, 1879-1955 -- Family -- Juvenile fiction; Einstein-Maric, Mileva, -- 1875-1948 -- Fiction; Einstein, Albert, 1879-1955 -- Fiction; Space and time -- Juvenile fiction; Space and time -- Fiction; Science fiction; Switzerland -- History -- 20th century -- Juvenile fiction; Serbia -- History -- 1804-1918 -- Juvenile fiction; Switzerland -- Fiction; Serbia -- Fiction; Science fiction